(untitled) (Scientific journal of the Fergana State University, 2025)
The article explores the role of the travelogue genre, particularly the work Travel Impressions, in the literary output of Munavvar Kori Abdurashidkhanov. The work is analyzed from a genre perspective, with a focus on the specific characteristics of the travelogue as a literary form. The poet’s journey to the city of Shymkent is examined in detail, and the genre-specific elements of the text are supported by scholarly analysis.